Peritoneal Dialysis–Related Peritonitis from Carbapenemase-Producing Klebsiella pneumoniae with OXA-48 Type Gene. Issue 1 (January 2019) - Ryanputra, Davin; Wang, Dingding; Lee, Martin B.; Teo, Boon Wee; Tok, Pei Loo
We report a rare case of carbapenemase-producing enterobacte-riaceae peritonitis in a patient undergoing automated peritoneal dialysis (APD). The PD catheter had to be removed as the patient remained unwell despite antibiotics. Antimicrobial resistance in PD peritonitis is a concern in this era of multi-drug resistant bacteria.